Knowledge and attitude of Mothers about Stunting in Banjar Pengukuh Peguyangan Kangin Village Denpasar - Ni Ketut Ayu Mirayanti; I Gede Juanamasta (Journal of Ners and Midwifery, 2020)
Childhood is a crucial period in the process of human growth and development. According to the Center for Data and Information of the Ministry of Health of the Republic of Indonesia (2018) stated the occurrence of a short toddler or commonly referred to as stunting is one of the nutritional problems experienced by toddlers in the world today. One of the determinants of the incidence of stunting in children under five years was the knowledge and attitude of the mother. The purpose of this research was to find out the description of the knowledge and attitudes of mothers with toddlers about Stunting in Banjar Pengukuh Peguyangan Kangin Village, Denpasar. The design of this study was cross-sectional. The sampling technique used nonprobability sampling with a purposive sampling approach, and the total sample wasÂ  68. In this study, the data analysis technique used the Univariate Analysis. Based on the analysis of the data obtained that the majority of respondents lacked knowledge of 44 people (64.7%) and had the right attitude, 66 people (97.1%). Suggestions for public health centre (puskesmas) to play an active role for disseminating stunting in schools and villages that will help reduce stunting indirectly.